The Sulu arms market national responses to a regional problem - Miani, Lino (Institute of Southeast Asian Studies, 2011)
Situated in a remote area long a historical buffer zone between competing political entities, the Sulu Arms Market is an illicit market of a typical form in that it is both a source and a destination for less-than-legal guns. What makes the Sulu market unique is its longevity which is measured in centuries. In modern times, guns from the area supply conflicts and crime from Japan to Sri Lanka to Papua New Guinea and beyond; and in turn the world pours guns and ammunition into Mindanao, the Maluku (Molucca) Islands, and to a lesser extent, Malaysia and the rest of the Philippines. Like most black arms pipelines, the Sulu Arms Market is intertwined with piracy, terrorism, and the traffic of other illicit commodities. Criminal gangs, communists, Moro independence groups, and Islamic militants are all major players in the market, making it a security problem for at least five member states of the Association of Southeast Asian Nations (ASEAN).